2016
DOI: 10.1088/2051-672x/4/2/024013
|View full text |Cite
|
Sign up to set email alerts
|

Development of low friction snake-inspired deterministic textured surfaces

Abstract: The use of surface texturization to reduce friction in sliding interfaces has proved successful in some tribological applications. However, it is still difficult to achieve robust surface texturing with controlled designer-functionalities. This is because the current existing gap between enabling texturization technologies and surface design paradigms. Surface engineering, however, is advanced in natural surface constructs especially within legless reptiles. Many intriguing features facilitate the tribology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 51 publications
0
26
0
1
Order By: Relevance
“…When comparing with the literature, it becomes apparent that frictional anisotropy of the laser-generated scale-like surface textures needs to be tested in the future. Such effects were reported for a variety of biological systems [ 55 56 ] and polymeric [ 21 22 ] as well as metallic [ 24 ] surface morphologies inspired by snake skin. Modelling efforts revealed that anisotropy is a function of the counter body’s surface roughness [ 56 ].…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…When comparing with the literature, it becomes apparent that frictional anisotropy of the laser-generated scale-like surface textures needs to be tested in the future. Such effects were reported for a variety of biological systems [ 55 56 ] and polymeric [ 21 22 ] as well as metallic [ 24 ] surface morphologies inspired by snake skin. Modelling efforts revealed that anisotropy is a function of the counter body’s surface roughness [ 56 ].…”
Section: Resultsmentioning
confidence: 84%
“…Researchers have started to look to biology in search for morphological textures that would allow for tribologically optimized surfaces [ 17 ]. Among the animals and biological structures that have been considered are butterfly wings [ 18 ], beetles and earthworms [ 19 ], scorpions [ 20 ] as well as (and most importantly) the skin of snakes and sand fish lizards [ 21 24 ]. It has been demonstrated, for example, that sandfish skin exhibits low friction and little wear [ 25 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main conclusion of these works is that reptile skin typically follows an aperiodic and asymmetric pattern, which is in contrast to the deterministic idea of surface texturing such as arranging dimples or other shapes in a regular matrix. It can be figured that by copying more ideas from nature, improved texture designs with superior friction and wear performance can be achieved [43,87]. The research group led by Greiner conducted research towards a similar direction thus copying the surface texture of snakes and lizards to optimize the friction response under dry and lubricated conditions.…”
Section: Effect Of Multi-scale Textures On Friction and Wear-experimementioning
confidence: 99%
“…The insights gained from the investigations of snake epidermis have inspired various design mimicking natural systems (Abdel-Aal and El Mansori, 2011; Abdel-Aal and El Mansori, 2013; Baum et al, 2014a; Baum et al, 2014b; Cuervo et al, 2016; Greiner and Schäfer, 2015; Mühlberger et al, 2015). For instance, it has been suggested that a surface texture resembling the scale microstructures of the Python regius is able to benefit the lubrication of cylinder liners (Abdel-Aal and El Mansori, 2011).…”
Section: Introductionmentioning
confidence: 99%